Evaluation of petrophysical heterogeneity of oil-gas reservoirs according to the data of geophysical studies of wells (Guneshly deposit as an example) - A. A. Feyzullayev; V. N. Lunina; G. T. Akhmedova (Геофизический журнал, 2017)
Investigations of the character of spatial variability of petrophysical properties of rocks, i. e. of their macro- and micro-heterogeneity are of special importance because they control the degree of saturation with fluids and intensity of fluid dynamics and are widely used for both calculation of resources and compiling the projects of development of oil-gas deposits. The article gives an evaluation of geological heterogeneity of rocks-collectors applying the data of geophysical studies of wells by the example of interruption suite (IS) of Guneshli deposit, which is the main oil-bearing object by the amount of its resources. A suite is represented by alternation of coarse- and medium-grained sands, sandstones and siltstones with thin argillaceous layers. The main parameters of macro-geterogeneity have been given by blocks in the whole IS, which were obtained by wells of the initial period of development: partitioning (the number of layers), thickness of one layer and overall thickness saturated with oil. In order to study heterogeneity of rocks-collectors applying the data of GSW relative amplitude of anomaly was chosen, which characterizes lithological and filtration-capacitive properties of rocks. Relationships of incipient yields of wells and coefficients of displacement of oil with parameters of heterogeneity of the layer-collector have been obtained. Effect of heterogeneity has been shown for factors of exhaustion of oil from the deposit. The studies conducted allowed to reveal the zones with better filtration-capacitive properties capable to be used for more objective rating of oil resources and the choice of optimal regime of development.